Assessing land-use history for reporting on cropland dynamics—A comparison between the Land-Parcel Identification System and traditional inter-annual approaches. (March 2016) - Zimmermann, Jesko; González, Ainhoa; Jones, Michael B.; O'Brien, Phillip; Stout, Jane C.; Green, Stuart
Highlights: The article explores the advantages and disadvantages of using the Land-Parcel Identification System (LPIS) in land-use/land-use change reporting. This is the first case study using 12 years full national LPIS coverage to assess short-term cropland/grassland dynamics. Using the example of cropland the study shows that LPIS has the potential to improve land-use/land-use change reporting. Major limitations in recognizing temporary grasslands when using annual reporting or comparison of consecutive years were identified. A methodology for identifying temporary grasslands using LPIS based land-use histories is introduced. Abstract: In developed countries, grassland and cropland conversion and management can be a major source of land-use and land-use change (LULUC) related greenhouse gas (GHG) dynamics. As this activity is recognized in the United Nations Framework Convention on Climate Change (UNFCCC), reporting on LULUC is an integral part of annual GHG inventories required from Annex I countries under the convention. In order to improve LULUC reporting, countries are shifting from national statistical data to high resolution spatial datasets. One such dataset is the Land-Parcel Information System (LPIS), an administrative spatial database developed to assist farmers and authorities assessing land eligibility for agricultural subsidies as part of the European Union's (EU) Common Agricultural Policy. Using the LPIS of the Republic of Ireland as a case study, we demonstrated significant differences in cropland/grassland reporting between an inter-annual based reporting schema and a land-use history approach. Twelve years of national LPIS data were analyzed to explore the dynamics between croplands and non-croplands. Major underlying cropland dynamics were identified with large areas changing between croplands and non-croplands even though annual total cropland areas were relatively stable over this period. Furthermore, we showed that in the 12 year study period, 69.8 ± 10.7% of the area leaving cropland each year returned to cropland within the following five years. Following the EU Common Agricultural Policy definition, these areas count as temporary grassland, which according to IPCC reporting guidelines should be reported as cropland. In an example utilizing three different LULUC reporting methodologies (total area based, land-parcel based, and land-use history based) to assess changes in cropland and grassland areas for the 2008–2012 GHG commitment period, not including land-use history led to an underestimation of cropland by 45.7% as well as an associated error in land-use change assessment. We therefore demonstrate good practice for accurately measuring cropland conversions under current IPCC guidelines using multi annual LPIS records.